Reduction in focal ictal activity following transplantation of MGE interneurons requires expression of the GABA(A) receptor α4 subunit - Jaiswal, Manoj K.; Keros, Sotirios A.; Zhao, Mingrui A.; Inan, Melis; Schwartz, Theodore H.; Anderson, Stewart A.; Homanics, Gregg E.; Goldstein, Peter A. (Frontiers in Cellular Neuroscience, 2015)
Despite numerous advances, treatment-resistant seizures remain an important problem. Loss of neuronal inhibition is present in a variety of epilepsy models and is suggested as a mechanism for increased excitability, leading to the proposal that grafting inhibitory interneurons into seizure foci might relieve refractory seizures. Indeed, transplanted medial ganglionic eminence interneuron progenitors (MGE-IPs) mature into GABAergic interneurons that increase GABA release onto cortical pyramidal neurons, and this inhibition is associated with reduced seizure activity. An obvious conclusion is that inhibitory coupling between the new interneurons and pyramidal cells underlies this effect. We hypothesized that the primary mechanism for the seizure-limiting effects following MGE-IP transplantation is the tonic conductance that results from activation of extrasynaptic GABAA receptors (GABAA-Rs) expressed on cortical pyramidal cells. Using in vitro and in vivo recording techniques, we demonstrate that GABAA-R α4 subunit deletion abolishes tonic currents (Itonic) in cortical pyramidal cells and leads to a failure of MGE-IP transplantation to attenuate cortical seizure propagation. These observations should influence how the field proceeds with respect to the further development of therapeutic neuronal transplants (and possibly pharmacological treatments).